VISUAL PROPAGANDA DURING SPANISH CIVIL WAR - A. A. Koroleva (Концепт: философия, религия, культура, 2017)
The article is devoted to the propaganda potential of political posters, created during the Spanish Civil War by republicans and nationalists. The Spanish Civil War is typically presented as a military narrative of the ideological battle between socialism and fascism, foreshadowing World War II. The art of posters was a massive manifestation of the art and public expression of ideologies. Republican posters appeared on the walls a few days after the war began. Political posters became important weapons in the battle for a free Spain. Visual propaganda creation and distribution processes of republicans and nationalists are compared. Propaganda uses messages to produce a more emotional rather than rational response to the information presented. Employing cultural studies methods to read propaganda posters as texts, symbols depicting how their meanings interacted with changing identities are analyzed. Principal concepts of ideology are represented in political posters; concept of sense of justice and geopolitical conspiracy. Republican posters were brighter, more varied and had a great mobilization effect. But republicans lacked a unified ideological line. Republican modernist experiments were not always clear to the viewer. Most part of republican and nationalist posters is characterized.